Does the Enlightened Youth Project See the Light? A New Enterprise for Youths at Risk - Cohen, Hanit (International journal of offender therapy and comparative criminology, 2021)
The aim of the present research is to examine the relationship between participation in the Enlightened Youth project for youths at risk and integration in employment at the end of the process, type of employment, dropout from school, and enlistment in the army. A database was prepared containing information on all the youths (499 in number) who were admitted to a multidisciplinary day Centre for Youths at Risk in Israel, of whom 86 participated in the project. To match a comparison group to the youths participating in the project, the propensity score matching method was operated. The research findings show a significant correlation between participation in the project and all the parameters examined, with implications regarding employment as a contributing factor among youths at risk, in terms of their personal lives, as well as financial and social well-being.